Administrative Law Innovation in Preventing Land Mafia Practices: Strengthening Public Governance in Indonesia: Inovasi Hukum Administrasi dalam Mencegah Praktik Mafia Tanah: Memperkuat Tata Kelola Publik di Indonesia - Etis Cahyaning Putri; Rudi Mulyanto (Indonesian Journal of Innovation Studies, 2026)
General Background: Systemic land-related crime in Indonesia undermines legal certainty, public trust, and the state’s constitutional responsibility to protect property rights through accountable agrarian administration. Specific Background: Organized networks exploit paper-based records, fragmented historical data, document falsification, bureaucratic collusion, overlapping certificates, and weaknesses within Indonesia’s negative publication system with positive tendencies. Knowledge Gap: Technological modernization alone does not explain how doctrinal reform, administrative safeguards, professional responsibility, and coordinated enforcement can collectively prevent state capture in agrarian governance. Aims: This study analyzes administrative law innovation for preventing organized property appropriation through digital transformation, registration doctrine reform, good governance principles, institutional restructuring, and interagency enforcement. Results: Using normative legal research enriched by socio-legal review, statutory, conceptual, comparative, and analytical case-study approaches, the study identifies cryptographically protected Electronic Land Certificates and Electronic Land Books as essential mechanisms for reducing physical document manipulation and preserving auditable ownership records. Their legal value, however, requires transition toward an absolute positive publication system based on indefeasible title, accompanied by a state indemnity fund for maladministration victims. Prevention also requires strict adherence to the General Principles of Good Governance, heightened due diligence by Land Deed Officials, proactive administrative revocation through contrarius actus, internal bureaucratic cleansing, and coordinated repressive enforcement. Novelty: The study integrates cryptographic administration, doctrinal reconstruction, professional gatekeeping, corrective discretion, and zero-tolerance institutional reform within a unified public governance framework. Implications: Sustainable prevention requires secure digital infrastructure, inclusive access, independent forensic audits, uncompromising bureaucratic integrity, and continuous cross-ministerial coordination. Highlights: Cryptographic certificates reduce document forgery and preserve traceable ownership records. AUPB compliance, heightened PPAT diligence, and contrarius actus enable rapid administrative correction. Zero-tolerance internal cleansing and cross-ministerial enforcement address state capture in agrarian governance. Keywords: Land Mafia, Administrative Law, Electronic Land Titles, Public Governance, Legal Certainty